A Research Study Exploring the Lived Experiences of Student Nurses Caring For The Dying Patient - Field, Jasmine (2009)
The primary aim of this study was to explore the lived experience of 2nd, 3rd and 4th year adult branch student nurses in caring for the dying patient. Caring for the dying is often a task that is presumed integral to the nurses role, however a substantial body of research exists to suggest that nurses at all stages of their careers feel uncomfortable and inadequately prepared in dealing with the dying patient and their family. Despite this student nurses are frequently expected to provide care to the dying, which has been shown to leave them with feelings of inadequacy, guilt and helplessness. This study adopted a qualitative methodology to fulfil its research aims, and used semi-structured interviews to facilitate the collection of data. The final sample consisted of 12 adult branch student nurses taken from both the diploma and masters programmes. All of the students were studying at the same teaching hospital, located in the east midlands. The data was analysed using Colaizzi’s (1978) analytical framework. The findings revealed two main themes: “Alleviating the discomfort” and “A pieced together approach in learning how to care”. The theme “Alleviating the discomfort” described how the student nurses efforts, when confronted with death were centered around taking precautionary measures, that would ensure their own distress would be minimised after the patient had died. The second theme “A pieced together approach in learning how to care” was informed by the student’s opinions of their university and life education so far. The overwhelming emphasis within this theme was how student’s felt their lives so far had rendered them ill equipped to care for the dying, and describes how the students had learnt to care for the dying by piecing together different facets of their university, practice and life experience.